KINERJA, KENDALA, DAN STRATEGI PROGRAM KREDIT USAHA RAKYAT SEKTOR PERTANIAN MASA DEPAN (Forum Penelitian Agro Ekonomi, 2021)
Agricultural funding institutions need capital business. The challenge of the Agriculture Sector Public Credit (ASPC) Program is to increase the program's reach, institutional, regulations, empowerment, and synergy among stakeholders. Some problems of the ASPC Program include low absorption rates, schemes, program coverage, assistance, and institutions. The future policy recommendations for the ASPC Program are providing a group-based credit scheme involving farmers groups and gapoktan, involving Agribusiness Micro Finance Institutions (AMFI) and cooperatives, extending bank branches, and providing companions. Recommendations for institutional and regulations need microprudential, better monitoring and evaluation system, guarantors’ availability, creating AMFI and cooperatives ratings, and strengthening legal instruments. Actions required to empower and strengthen the synergy are supporting the Independent Smallholder Financing Facilitator (ISFF) role, special agricultural sector programs (people’s plantation and livestock) with the ceiling adjusted to the proposal, joint responsibility, and business partner. Cooperation with the field agriculture extension is necessary for socialization among the farmer's group and gapoktan. The provincial and district technical team's role is to monitor ISFF's performance.